2018
DOI: 10.1177/0194599817751678
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction Value of the Systemic Inflammation Score for Oral Cavity Squamous Cell Carcinoma

Abstract: Objectives This study aimed to investigate the potential prognostic role of the oral cancer systemic inflammation score (SIS) based on serum albumin levels and the lymphocyte-to-monocyte ratio in patients with oral squamous cell carcinoma (OSCC) after treatment. Study Design A retrospective cohort study. Setting Tertiary care center. Subjects and Methods The study involved 613 patients who were treated for OSCC between September 2005 and December 2014. The association of the oral cancer SIS with various clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Both the serum albumin concentration and the LMR, which are components of the SIS, are markers related to inflammation, but their severity is not always correlated with each other (11). Therefore, the combination of these two markers enables a more detailed stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the serum albumin concentration and the LMR, which are components of the SIS, are markers related to inflammation, but their severity is not always correlated with each other (11). Therefore, the combination of these two markers enables a more detailed stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is known to contribute to cancer progression (1,2), and several inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR), the lymphocyte-to-monocyte ratio (LMR) and the Glasgow prognostic score (GPS) have been reported to be associated with clinical outcomes in patients with various types of cancer, including colorectal cancer (3)(4)(5)(6)(7)(8). Recently, a new inflammatory marker, the systemic inflammatory score (SIS), based on the combination of the LMR and the serum albumin concentration has been reported to be a useful prognostic marker in patients with clear-cell renal cell carcinoma, colorectal cancer and oral cavity squamous cell carcinoma (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These updated prognostic variables would not be available for the older AJCC staging systems. However, we found several studies using older editions of the AJCC staging, which also feature “contemporary” prognostic variables such as HPV or ENE as components of their nomograms. The c‐indexes of these studies (maximum 0.83) were just as high as the c‐indexes of studies using the 8th AJCC edition (maximum 0.76).…”
Section: Discussionmentioning
confidence: 99%
“…The level of agreement for the second phase was 88% with a kappa of 0.77. A total of 44 studies remained for the final analysis . The list of excluded papers with the reasons for exclusion can be found in the Supporting Information S3.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, stromal fibroblasts may play a vital role in the desmoplastic reaction to cancer by secreting the extracellular matrix. Eltohami et al [43] reported that the systemic inflammatory score (SIS), which is based on the sum of albumin and the lymphocyte-to-monocyte ratio, is closely associated with local progression (T grade), clinical stage, tumor depth, perineural invasion, extranodal extension, and poor survival. Cyclooxygenase-2 (COX-2) is a pro-inflammatory enzyme that converts arachidonic acid to prostaglandins, promoting invasion and OSCC cell metastasis [44].…”
Section: Hallmarks Of Cancer-related Conventional Principal Prognomentioning
confidence: 99%